Enhancing Critical and Creative Thinking through Research-Based Learning: The CCTRbL Model's Impact on Student Abilities - Mawardi Mawardi; Dani Kusuma (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing critical and creative thinking skills is essential for prospective teachers to meet 21st-century education demands. However, these skills remain relatively low among teacher education students. This study investigates how higher education institutions can design learning experiences to foster these competencies, focusing on the Creative and Critical Thinking in Research-based Learning (CCTRbL) model. This study employed an action research approach based on a modified Burn model, comprising five stages: (1) Identifying, (2) Planning, (3) Intervening, (4) Observing, and (5) Reporting. The participants were 27 teacher education students. Data were collected using an integrated critical and creative thinking assessment rubric for evaluating students’ research-based paper tasks. Data analysis utilized categorical descriptive techniques and percentage calculations. The findings indicate that the CCTRbL model effectively enhances students' critical and creative thinking skills, with scores of 68.29 and 65.18, respectively, categorized as high. This suggests that the implemented model positively impacts students' ability to think critically and creatively. The study demonstrates that integrating critical and creative thinking in a research-based learning framework is beneficial for teacher education programs. The findings suggest that the CCTRbL model can be adapted for use at different educational levels with modifications suited to subject-specific requirements. The CCTRbL model is a promising approach to fostering critical and creative thinking skills in teacher education. It is recommended for broader application in primary, secondary, and higher education to enhance students' cognitive abilities and professional competencies.